Detrimental Effects of Tartrazine on Oral Mucosal Tissues of Wistar Albino Rats: An Experimental Study (Medical Forum Monthly, 2023)
Objective: To evaluate the detrimental effects of Tartrazine on oral mucosal tissues of Wistar Albino rats.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Department of Oral Biology, Karachi Medical and Dental College (KMDC), Sindh from March-May 2023.Materials and Methods: After approval from the Ethical & Scientific Review Committee, KMDC. Eighteen adult healthy male and female Wistar albino rats, weighing 180–200 grams were used and kept in temperature controlled room with a typical 12h light-dark cycle at a temperature of 23°C for two weeks of acclimatization. Animals were randomly clustered into three equal groups (A, B, and C). Group B and C (experimental groups) rats were given Tartrazine at doses of 7.5, and 15 mg/100gm body weight respectively for 60 days while group A (Control group) was given a normal chow diet along with distilled water. Biochemical and Histopathological analysis of oral mucosal tissue of all groups was performed after 60 days.Results: Significant decline (p<0.05) in body weight of group B and C rats compared to group A rats. A statistically significant difference in antioxidant levels (GPX, SOD, and CAT) with post-hoc turkeys (p<0.05) was observed between group C compared to group B and A rats. While a marked histo-pathological alteration of oral mucosal tissue (keratinization, Acanthosis, dilatation of the minor salivary ducts, and neutrophil infiltration) was demonstrated in group C rats compared with group B and A rats.Conclusion: Tartrazine in increased doses has a considerable influence on histological, morphological, and immune-histochemical degenerative effects on the oral mucosal tissues.